Trend analysis of principal candidate training based on scopus data (2020–2024): Mapping leadership, digital transformation, and educational innovation using vosviewer - R A Mustika Hariyanti; Agus Pahrudin; Muhammad Akmansyah; Ahmad Fauzan (Balai Diklat Keagamaan Ambon, 2026)
This study aims to analyze trends in scientific publications on principal candidate training using Scopus-indexed data from 2020 to 2024, employing a bibliometric approach supported by VOSviewer. The analyzed articles were selected based on the following relevance criteria: (1) indexed in Scopus, (2) published between 2020 and 2024, (3) directly discussing principal candidate training, educational leadership, or principal competency development, and (4) related to leadership transformation and educational innovation. This study was motivated by the growing need to strengthen school leadership competencies in the era of digital transformation and by the limited number of bibliometric studies that specifically map the development of research on principal candidate training. The research employed a qualitative descriptive method combined with bibliometric analysis. Data were collected using the Publish or Perish application integrated with the Scopus database, with keywords related to principal candidate training, school leadership training, and educational leadership development. The article selection process resulted in 20 publications that met the inclusion criteria. The findings indicate that publication trends have increased significantly since 2021, with major research focuses on transformational leadership development, managerial competencies, the effectiveness of principal training programs, and the integration of digital transformation in educational leadership. The VOSviewer analysis identified four major clusters demonstrating relationships among leadership style, transformational leadership, school leadership, candidate principals, school counsellors, and supervisors. The study reveals a shift in research orientation from traditional administrative leadership to innovative, technology-based educational leadership in the era of the Industrial Revolution 4.0. This research contributes theoretically to strengthening the mapping of educational leadership studies and serves as a strategic reference for developing future principal candidate training programs.